2009
DOI: 10.1021/jp8098347
|View full text |Cite
|
Sign up to set email alerts
|

Ag Site in Ag-for-Na Ion-Exchanged Borosilicate and Germanate Glass Waveguides

Abstract: The Ag site in Ag-for-Na ion-exchanged borosilicate and germanate waveguides has been investigated by EXAFS spectroscopy. In contrast with the results generally reported in literature, it is shown that, for both silicate and germanate waveguides, the Ag site is strongly dependent on the Ag content and the Ag-O distance is longer for higher doping levels. It is demonstrated that this trend is related to a structural rearrangement of the Ag site in the whole doped layer; the EXAFS results on the samples that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Nevertheless, if this would be the case, the effective coordination number of this O shell would be about 3-4 for at least two cases, to be compared with the coordination number of ≈2 experimentally found for other noble metal ions, such as Ag, introduced in solid glass matrices. 17 Considering also that the Gibbs free energy for Auoxide formation is the highest among those of transition metal oxides, a O coordination at the cluster surface seems to be more reasonable, further supporting the picture of core-shelllike clusters. The Au-O coordination distance varies in a nonmonotonic way (Table 1) with the annealing temperature.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, if this would be the case, the effective coordination number of this O shell would be about 3-4 for at least two cases, to be compared with the coordination number of ≈2 experimentally found for other noble metal ions, such as Ag, introduced in solid glass matrices. 17 Considering also that the Gibbs free energy for Auoxide formation is the highest among those of transition metal oxides, a O coordination at the cluster surface seems to be more reasonable, further supporting the picture of core-shelllike clusters. The Au-O coordination distance varies in a nonmonotonic way (Table 1) with the annealing temperature.…”
Section: Resultssupporting
confidence: 52%
“…X-ray absorption spectroscopy (XAS) performed at the metal edge is a suitable technique to monitor metal nucleation and the first steps of growth since it can detect both oxide phases 17 and the formation of clusters, 14,18 even in the sub-nanometer range of size. 19,20 In the case of monodisperse clusters, a detailed analysis can also give an indication of the cluster shape.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ag K-edge EXAFS analysis showed that Ag + ion had a CN of 2.1 with a Ag-O distance of 2.08 Å [31]. The similar behavior could be observed in other glasses [32,33]. It means that the Ag incorporation always causes local structural relaxations.…”
Section: +supporting
confidence: 58%
“…From the EXAFS results, therefore, and considering Au and Au-Ag clusters with roughly the same size equation, which relates the interatomic distance variation to the cluster size, 18,31 we can estimate that the pure Au N and the alloy in Ag-based glass waveguides under conditions of slight supersaturation, i.e., at the onset of the Ag nucleation. 32,33 This suggests that at least part of Ag atoms at the cluster surface is covalently connected to O atoms of the matrix.…”
Section: Resultsmentioning
confidence: 99%